Early modern prophecies in transnational, national and regional contexts - Laborie, Lionel; Hessayon, Ariel (Brill's studies in intellectual history, 2021)
v. 1. Continental Europe -- v. 2. The Mediterranean world -- v. 3. The British Isles.